2018
DOI: 10.1186/s12882-018-1041-z
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate dietary energy intake associates with higher prevalence of metabolic syndrome in different groups of hemodialysis patients: a clinical observational study in multiple dialysis centers

Abstract: BackgroundMetabolic syndrome (MetS) has been established as a risk for cardiovascular diseases and mortality in hemodialysis patients. Energy intake (EI) is an important nutritional therapy for preventing MetS. We examined the association of self-reported dietary EI with metabolic abnormalities and MetS among hemodialysis patients.MethodsA cross-sectional study design was carried out from September 2013 to April 2017 in seven hemodialysis centers. Data were collected from 228 hemodialysis patients with accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 79 publications
2
10
0
Order By: Relevance
“…In comparison with previous studies, the percentages of patients consuming low dietary energy (69%) were close to that in a study in Taiwan (60%) using a 3-day dietary intake record, but lower than that being reported in Poland (80%) using a dietary questionnaire. 24,25 This study also showed that almost twothirds of patients consumed less protein than recommended, which is consistent with the results from the Poland study. 25 The relatively few patients who consumed enough protein could be explained by the restriction of dietary phosphorus intake.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In comparison with previous studies, the percentages of patients consuming low dietary energy (69%) were close to that in a study in Taiwan (60%) using a 3-day dietary intake record, but lower than that being reported in Poland (80%) using a dietary questionnaire. 24,25 This study also showed that almost twothirds of patients consumed less protein than recommended, which is consistent with the results from the Poland study. 25 The relatively few patients who consumed enough protein could be explained by the restriction of dietary phosphorus intake.…”
Section: Discussionsupporting
confidence: 90%
“…The mean daily protein and energy intake of our patients did not achieve the target recommendations for clinically stable hemodialysis patients, especially on NDDs. In comparison with previous studies, the percentages of patients consuming low dietary energy (69%) were close to that in a study in Taiwan (60%) using a 3‐day dietary intake record, but lower than that being reported in Poland (80%) using a dietary questionnaire . This study also showed that almost two‐thirds of patients consumed less protein than recommended, which is consistent with the results from the Poland study .…”
Section: Discussionsupporting
confidence: 88%
“…More than half of hemodialysis patients have problems following healthy dietary guidelines (related to energy and nutritional intake) related to behavior, technical difficulties, physical condition, time and food preparation. Inadequate food intake is also a result of significant lifestyle changes when receiving dialysis treatment (6) . Furthermore, this research was in line with Sharif's research (7) which states that there is no correlation between energy intake and nutritional status in patients with chronic renal failure with hemodialysis in Wahidin Sudirohusodo Hospital, Makassar, Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…The dietary data were assessed using the 24-hour dietary recall form in paper format [22]. A qualified dietician instructed patients to complete the assessment forms on one dialysis day, one non-dialysis day, one non-dialysis day during the weekend, including meal time, meal location, food name, brand names, ingredients, portion or weight of food, and the cooking methods, oils used [20,23]. To confirm the data collected, dietitians used the 24-hour dietary recall form with common utensils to ask patients face-to-face or by phone call, as described previously [20,23,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Restrictive dietary approaches are one of the causes [40]. Therefore, adequate energy and protein intake are critically important in securing the nutritional status of hemodialysis patients [23,29]. The total grain consumption and total protein intake were suggested based on the level of energy requirements according to the Daily Food Guides [7].…”
Section: Methodsmentioning
confidence: 99%